Processing different kinds of semantic relations in picture-word interference with non-masked and masked distractors - Damian, Markus F.; Spalek, Katharina (Frontiers in Psychology, 2014)
Spoken production requires lexical selection, guided by the conceptual representation of the to-be-named target. Currently, the question whether lexical selection is subject to competition is hotly debated. In the picture-word interference task, manipulating the visibility of written distractor words provides important insights: clearly visible categorically related distractors cause interference whereas masked distractors induce facilitation (Finkbeiner, M., & Caramazza, A., 2006. Now you see it, now you don’t: On turning semantic interference into facilitation in a Stoop-like task. Cortex). We explored the effect of distractor masking in more depth by investigating its interplay with different types of semantic overlap. Specifically, we contrasted categorical with associatively based relatedness. For the former, we replicated the polarity reversal in semantic effects dependent on whether distractors were masked or not. Post-experimental visibility tests showed that weak semantic facilitation with masked distractors did not depend on individual variability in participants’ ability to perceive the distractors. Associatively related distractors showed facilitation with non-masked presentation, but little effect when masked. Overall, the results suggest that it is primarily distractor activation strength which determines whether semantic effects are facilitatory or interfering in PWI tasks.